2019
DOI: 10.1080/22221751.2019.1661217
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous shedding of multiple bat paramyxoviruses coincides with peak periods of Hendra virus spillover

Abstract: Within host-parasite communities, viral co-circulation and co-infections of hosts are the norm, yet studies of significant emerging zoonoses tend to focus on a single parasite species within the host. Using a multiplexed paramyxovirus bead-based PCR on urine samples from Australian flying foxes, we show that multi-viral shedding from flying fox populations is common. We detected up to nine bat paramyxoviruses shed synchronously. Multi-viral shedding infrequently coalesced into an extreme, brief and spatially r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 59 publications
4
55
1
1
Order By: Relevance
“…Since temporal fluctuation of viral load has been documented in virus surveillance of north American and European microbats [96,97] as well as Hendra shedding in Australian peteropid bats [22,98], longitudinal studies would be required to fully understand the viral shedding and viral-host associations observed here. Furthermore, evidence of higher viral loads as indicators of individual and population scale stress [10] provides a good example of how long-term monitoring of viral prevalence can act as an indicator of environmental pressure on bat communities, particularly with regards to climate change where habitat contracture and distributional shifts may bring together populations harbouring novel viral strains.…”
Section: Discussionmentioning
confidence: 98%
“…Since temporal fluctuation of viral load has been documented in virus surveillance of north American and European microbats [96,97] as well as Hendra shedding in Australian peteropid bats [22,98], longitudinal studies would be required to fully understand the viral shedding and viral-host associations observed here. Furthermore, evidence of higher viral loads as indicators of individual and population scale stress [10] provides a good example of how long-term monitoring of viral prevalence can act as an indicator of environmental pressure on bat communities, particularly with regards to climate change where habitat contracture and distributional shifts may bring together populations harbouring novel viral strains.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, datasets such as the one we used here are commonly generated by many multipathogen surveillance and multi-species monitoring programmes, and so our method can be easily applied to a variety of contexts. Indeed, other critical examples of our methodology have already demonstrated that viral co-infections provide insights into the timing of Hendra virus emergence events [54] and that the compositions of avian blood parasite communities, marshland arthropod communities and wildlife microbiome profiles are the products of complex factors including biotic associations and environmental variation [33,55]. However, a drawback of the CRF approach is that prediction of infection risk for unsampled areas is challenging due to the requirement that at least some parasite presence-absence information needs to be available for the unsampled area.…”
Section: Conditional Random Fields To Model Infection Riskmentioning
confidence: 99%
“…There is evidence to suggest that two species, namely the Black flying fox (Pteropus alecto) and the Spectacled flying fox (P. conspicillatus), play the most active role in the transmission of Hendra virus to horses [38]. Hendra virus is shed in the urine, an important vehicle for transmission in Black flying foxes [10,[38][39], and the virus has been detected in Grey-headed flying fox uterine fluid which provides evidence for possible transmission at birthing period which lasts from late September to early December [40] in this species [41,42].…”
Section: Introductionmentioning
confidence: 99%